Increasing cocoa productivity and farmer capacity in surrounding area of PT Kaltim Prima Coal and PT Berau Coal - J B Baon; A A Prawoto; A Wibawa; S Abdoellah (Brawijaya University, 2014)
Based on agro-climate factors, most of surrounding area of coal mining sites in Indonesia is suitable for cocoa cultivation. However, most of cocoa farmers in the environs of coal mining sites have little access both to new technology of cocoa cultivation and to market of their cocoa products. Therefore, productivity of cocoa farms and the income of cocoa farmers are low, which may disturb social responsibility of the coal mining companies present in their surroundings. These are the consequences of poor interaction between the government, private sector and research sector. The aim of this study is to transfer and to implement good agricultural practices of cocoa in surrounding area of mining sites of Kaltim Prima Coal (KPC) and Berau Coal (BC), East Kalimantan, in order to increase farmer capacity and cocoa productivity. Indonesian Coffee and Cocoa Research Institute as the developing agent of cocoa technology has established collaboration with corporate social responsibility program of KPC (already 7 years) and BC (already 2 years) to improve productivity and farmer capacity of cocoa farms surroundings the two cocoa mining companies. This paper discusses the aspects of natural, economic and human resources; baseline study; technology transfers; marketing partnership; cocoa productivity; farmer income after technology implementing; study of cocoa growth on post-coal-mining. It is concluded that improvement of the cocoa productivity and farmer capacity surroundings the two mining sites associated with high adoption of technology by farmers, better access to availability of knowledge for good agricultural practices, extension officers, demonstration plots, cocoa price, and length of market chains, partnership, and competition with oil palm plantations.